2011
DOI: 10.1021/ic1025679
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Modulation of a Bichromic Cyclometalated Ruthenium(II) Scaffold Bearing a Redox-Active Triphenylamine Constituent

Abstract: The syntheses and physicochemical properties of nine bis-tridentate ruthenium(II) complexes containing one cyclometalating ligand furnished with terminal triphenylamine (TPA) substituents are reported. The structure of each complex conforms to a molecular scaffold formulated as [Ru(II)(TPA-2,5-thiophene-pbpy)(Me(3)tctpy)] (pbpy = 6-phenyl-2,2'-bipyridine; Me(3)tctpy = trimethyl-4,4',4''-tricarboxylate-2,2':6',2''-terpyridine), where various electron-donating groups (EDGs) and electron-withdrawing groups (EWGs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 69 publications
4
66
0
Order By: Relevance
“…134 However, Berlinguette showed that the emissive behaviour of [8b] + actually arises from a singlet intraligand charge transfer state ( 1 ILCT) involving the diarylamine unit as electron donor and the polypyridine moiety as electron acceptor. 165,166 An identical emission energy was observed for the free ligand with even higher fluorescence quantum yields (ϕ = 0.91, τ = 3.4 ns) explaining the untypically high emission energy and quantum yield of [8b] + . [164][165][166] To get a better understanding of the states involved in the excited state deactivation of [Ru(tpy)( pbpy)] + complexes, we studied the triplet potential energy surface of [7a] + using DFT calculations.…”
Section: The [Ru(n^n^n)(n^n^c)] + Coordination Spherementioning
confidence: 71%
“…134 However, Berlinguette showed that the emissive behaviour of [8b] + actually arises from a singlet intraligand charge transfer state ( 1 ILCT) involving the diarylamine unit as electron donor and the polypyridine moiety as electron acceptor. 165,166 An identical emission energy was observed for the free ligand with even higher fluorescence quantum yields (ϕ = 0.91, τ = 3.4 ns) explaining the untypically high emission energy and quantum yield of [8b] + . [164][165][166] To get a better understanding of the states involved in the excited state deactivation of [Ru(tpy)( pbpy)] + complexes, we studied the triplet potential energy surface of [7a] + using DFT calculations.…”
Section: The [Ru(n^n^n)(n^n^c)] + Coordination Spherementioning
confidence: 71%
“…The band maximum was observed at 905 mV vs NHE, and was centred at 20,620 cm −1 (485 nm). The extinction coefficients used for the structural analogue of 1p were observed at 18,800 cm −1 (532 nm) and 22,780 cm −1 (439 nm) with reported values of 32.8 × 10 3 and 44.9 × 10 3 M −1 cm −1 , respectively 49 . The approach used to calculate the IVCT extinction for 1p was the same as that for 2p.…”
Section: Methodsmentioning
confidence: 94%
“…Five unique Gaussian fits of the band yielded values for E abs (vide supra) and Δν 1/2 . ε max was estimated from the extinction coefficient of a structurally similar compound at 19,230 cm −1 (520 nm) and 23,200 cm −1 (431 nm) with extinction coefficients of 41.5 × 10 3 and 39.1 × 10 3 M −1 cm −1 , respectively 49 . Under the assumption that the number of 2p molecules in the intervalence state is equal to the number in the ground state (that is, a complete one e -oxidation to the mixed valence state), a ratio of absorbance values and extinction coefficients was employed, and ten values of H AB were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…They are 4'-di-p-anisylamino-2,2':6',2"-terpyridine (daatpy), [12] 4'-tolyl-2,2':6',2"-terpyridine (ttpy), [13] 4'-nitro-2,2':6',2"-terpyridine (NO 2 tpy), [14] and trimethyl-4,4',4"-tricarboxylate-2,2':6',2"-terpyridine (Me 3 tctpy). [15] The ligand daatpy is substituted with an electron-donating amine group, whereas NO 2 tpy and Me 3 tctpy have electronwithdrawing substituents. They were deliberately selected to vary the electronic properties of resulting complexes.…”
Section: Synthesismentioning
confidence: 99%
“…These waves are within the typical potential window for cyclometalated ruthenium complexes with a [Ru(N 5 C)] coordination sphere. [15,16] The presence of the anionic cyclometalating phenyl ring in these complexes generally shifts the Ru III/II process to a much less positive potential window, with respect to conventional ruthenium complexes with a RuN 6 coordination sphere.…”
Section: Electrochemical Studiesmentioning
confidence: 99%